Enhancing Talent Attraction and Retention Through Strategic Recruitment Policy Innovation in Modern Organizations - Syamsul Bahri; Moh. Zulkifli Murfat; Dilshodbek A. Rakhimov (Vifada Management and Social Sciences, 2025)
This study examines how strategic recruitment policy innovation enhances talent attraction and retention in modern organizations facing rapid digital, demographic, and competitive shifts. As firms confront increasing skill shortages and dynamic workforce expectations, innovative recruitment policies—such as data-driven hiring, employer branding optimization, candidate experience enhancement, and competency-based selection—are viewed as critical drivers of organizational talent outcomes. Using a mixed-method approach involving survey responses from 328 HR professionals and interviews with 22 recruitment managers across technology, financial services, and public-sector organizations, the findings reveal that recruitment innovation significantly improves talent attraction, with employer branding and digital recruitment platforms acting as the strongest predictors. Retention is positively influenced by personalized onboarding systems, transparent career pathways, and alignment between organizational values and candidate expectations. Additionally, digital recruitment analytics moderates the relationship between policy innovation and overall recruitment effectiveness. The study offers practical insights for HR leaders to redesign recruitment frameworks that integrate technology, human-centered design, and strategic workforce planning to strengthen long-term talent sustainability.